Global Optimal Solutions for Proximal Fuzzy Contractions Involving Control Functions - Abdelhamid Moussaoui; Nawab Hussain; Said Melliani (Journal of Mathematics)
In this study, we introduce new concepts of α−FZ-contraction and α−ψ−FZ-contraction and we discuss existence results of the best proximity points of such types of non-self-mappings involving control functions in the structure of complete fuzzy metric spaces. Our results extend, generalize, enrich, and improve diverse existing results in the current literature.